Optimal Bounds for Neuman-S´andor Mean in Terms of the Convex Combination of Geometric and Contra-harmonic Means - Haibin, He; Chunrong, Liu (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this paper, we present the least value α and the greatest value β such that the double inequality αG(a, b) + (1 − α)C(a, b) < M(a, b) < βG(a, b) + (1 − β)C(a, b) holds for all a, b > 0 with a 6= b, where G(a,b), M(a,b) and C(a,b) are respectively the geometric, Neuman-S´andor and contra-harmonic means of a and b.